Abstraction : Documents of Contemporary Art. - Lind, Maria; Barr, Alfred H.; Blom, Ine; Cooke, Lynne; Davies, Anthony; Freeman, Judi; Halley, Peter; Houston, Joe; Jameson, Frederic; Lippard, Lucy R.; Lütticken, Sven; Möntmann, Nina; et al. (Londen : Whitechapel Gallery, 2013)
Albers, Anni ; Bourgeois, Louise ; Buren, Daniel ; de Castro, Amilcar ; Clark, Lygia ; Dahlberg, Kajsa ; Dillemuth, stephan ; Einarsson, Gardar Eide ; Förg, Günther ; Gillick, Liam ; Hesse, Eva ; Jakobson, Jakob ; Judd, Donald ; Klein, Yves ; de koning, Krijn ; Lewitt, Sol ; Lohse, Richard paul ; Mondrian, Piet ; Nauman, Bruce ; Oiticica, Hélio ; Palermo, Blinky ; Pape, Lygia ; Perret, Mai-Thu ; Rehberger, tobias ; Riley, Bridget ; Rothko, Mark ; Roysdon, Emily ; Ryman, Robert ; Schendel, Mira ; Stanczak, Julian ; Stepanova, Varvara ; Steyerl, Hito ; Twombly, Cy
Formal abstraction, economical abstraction from the global market and media operations, social abstraction, new possibilities for art and society
boek